The ichnology of shallow-marine and transitional environments - Cónsole Gonella, Carlos Alfredo (2023)
The ichnology between marine and non-marine environments is a key field of work concerning theunderstanding of the variation of environmental parameters in inland-to-offshore transitional environments. Inorder to understand the geological and palaeobiological processes at these locations, this Special Publicationattempts to discuss records in shallow-marine and transitional environments throughout the Phanerozoic,including topics such as ichnotaxonomy, ichnofacies analysis, ichnofabric analysis for records from both shallow-marine and transitional environments, and neoichnological aspects. The volume includes 14 papers in total:one focused on aspects of neoichnology in rock iguanas in coastal settings, nine concerning various shallowmarinepalaeoenvironment topics and four addressing issues about dinosaur tracks in transitional environments.